Factors influencing rubber price in Malaysia under diffrent economic condition / Muhammad Izzat Amer Hamzah - Amer Hamzah, Muhammad Izzat (2012)
This paper studies the factors influencing rubber price in Malaysia under different economic condition. These effects were measured using Multiple Linear Regression to determine the result of the model. Under normal economic condition, there are two factors that significant which are currency exchange and supply of natural rubber. While the crude oil price is insignificant. In economic crisis, there are also two variables that influencing rubber price. They are crude oil price and currency exchange. The other variable which is supply of natural rubber is insignificantly influencing rubber price in Malaysia. as a whole, all independent variables used in this study; crude oil price, currency exchange and supply of natural rubber are significantly affect the prices of rubber in Malaysia